P39-S Multimodal evoked potentials in patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). Issue 7 (July 2019) - Dziadkowiak, Edyta; Ejma, Maria; Wieczorek, Malgorzata; Pec, Pawel; Slotwinski, Krzysztof; Budrewicz, Slawomir; Zimny, Anna; Koszewicz, Magdalena
Abstract : Background: The central nervous system in chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is involved in about 5% of patients. The aim of the study was the assessment of the prevalence of central sensory impairment, and its reliance on peripheral nerve damage in patients with CIDP. Materials and methods: The study group consisted of 24 patients with mean age of 60.7, who fulfilled the diagnostic criteria of typical form of CIDP at the time of multimodal (visual - VEP, brainstem auditory - BAEP, somatosensory SEP) evoked potentials (EPs) study. Each patient underwent a neurological examination, as well as a CT/MRI scan of the head. The evoked potentials was conducted according to the International Federation of Clinical Neurophysiology (IFCN) guidelines. Results: Mean latency of most components of EP were considerably prolonged in patients compared to the control group. Negative correlations of SNAP amplitudes and sensory conduction velocities in peripheral nerves were obtained for I-V and III-V inter-latencies BAEP, for N20, P16, P22 SEP and the central conduction time TT for all sensory fibers of the left upper limb nerves. Conclusions: Correlations of SNAP and EP parameters indicate subclinical damage to the central sensory pathways. The CIDP pathomechanism is still unclear and needs further research.